Gen Z Purchasing Decisions Through Brand Awareness and Consumer Preferences: The Moderating Role of Social Media Influencers - Putri, Reina Aurelia; Junipriansa, Donni (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Gen Z, a generation highly engaged with the digital world, demonstrates unique consumption behaviors shaped by various external influences. The digital lifestyle of Generation Z makes social media a key space for shaping perceptions and purchasing decisions.Purpose: This study explores the primary factors affecting Gen Z's purchasing decisions, emphasizing the roles of brand awareness and consumer preferences. Additionally, it assesses whether social media influencers strengthen or weaken these relationships.Design/methodology/approach: This study surveyed 170 Gen Z social media users in Indonesia, using a purposive sampling method. The research instrument was an online questionnaire distributed through Google Forms, consisting of several statements measured using a 5-point Likert scale (1 = strongly disagree to 5 = strongly agree). The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.0.9.Findings/Result: The results show that brand awareness has a positive and significant effect on Gen Z purchasing decisions, with a Path Coefficient of 0.415 and a P-value of 0.000 ( 0.05). Meanwhile, the social media influencers variable has a positive and significant influence on Gen Z purchasing decisions, with a Path Coefficient value of 0.387 and a P value of 0.000 (